Regulatory aspects and evidences of melatonin use for sleep disorders and insomnia: an integrative review - Ana Paula Rosinski Bueno; Flávia Medeiros Savi; Izabel Almeida Alves; Vanessa Adelina Casali Bandeira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Insomnia is a sleep disorder characterized by difficulty of falling asleep or maintaining sleep, which affects different age groups. Currently, melatonin is used as a therapeutic treatment in cases of insomnia in children, adults, and elderly people. Objective: To evaluate the effectiveness of melatonin in sleep disorders, its dosage, potential adverse effects, as well as labeling laws and regulations in Brazil. Methods: This integrative review was carried out using the Cochrane Library, Medline (Pubmed), and Science Direct databases. Twenty-five articles and three documents available on the Brazilian Society of Endocrinology and Metabology (SBEM) and National Health Surveillance Agency (ANVISA) websites published between 2015 and 2020 were selected to be evaluated in full. Results: It was found that in most of the selected articles the use of melatonin reduces sleep latency. The effective melatonin doses varied according to each age group, from 0.5 to 3 mg in children, 3 to 5 mg in adolescents, 1 to 5 mg in adults, and 1 to 6 mg in elderly people. Side effects are mild when taking usual doses. In Brazil, no registered drug and current regulation on the use and marketing of melatonin has been identified. Conclusion: The use of melatonin is an alternative therapy that can be used for sleeping disorders. According to the evidences found, it did not demonstrate toxicity or severe side effects, nor dependence even when administered at high doses, suggesting that it is a safe medication to treat patients of different ages suffering from sleeping disorders.